(untitled) (Plant Tissue Culture and Biotechnology, 2020)
An effort was made to identify the in vitro responsiveness for callus induction in NaCl (salt stress) and subsequent plant regeneration of oats (Avena sativa L.). Callus induction was tested in different concentrations (0, 5, 10, 15 and 20 mg/l) of NaCl salt added in MS. The experiment was laid out in CRD considering 2,4-D growth regulator and NaCl salt as factors. The best response in callus induction was observed on MS containing 3 mg/l 2,4- D and 5 mg/l NaCl where the frequency of callus induction was 68.57%, callus weight was 0.36 g and callus diameter was 7.63 mm. During regeneration, the maximum frequency of regeneration (41.67%), regenerated shoots per callus (14.80), shoot length (12.14 cm), root number (10.90) and root length (3.76 cm) was observed from the callus derived from MS containing 3 mg/l 2,4-D and 5 mg/l NaCl. Plantlets that were regenerated from callus induced in MS with 3 mg/l 2,4-D and 5 mg/l NaCl showed higher rate of ex vitro survivability. Therefore, MS with 3 mg/l 2,4-D and 5 mg/l NaCl found better for in vitro callus induction and subsequent plant regeneration from mature seeds of oat. Plant Tissue Cult. & Biotech. 30(2): 253-266, 2020 (December)